1972
DOI: 10.1111/j.1476-5381.1972.tb08134.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological actions of a new β‐adrenoceptor agonist, MJ‐9184–1, in anaesthetized cats

Abstract: Summary The effects of (–)‐isoprenaline and the new β‐adrenoceptor agonist, MJ‐9184–1, on the lungs, on the cardiovascular system, and on slow contracting skeletal muscle have been compared in cats under chloralose anaesthesia. Both amines reduced the increases in airways resistance produced by 5‐HT, depressed incomplete tetanic contractions of the soleus muscle, lowered the blood pressure and produced an increase in heart rate. In comparison with (‐)‐isoprenaline, MJ‐9184–1 had a long duration of action. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

1974
1974
1996
1996

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…Marsden et al (1967) have shown an increase in physiological tremor with isoprenaline and have demonstrated a blockade of this induced tremor by propranolol, suggesting that a 3 receptor may be involved. Animal studies have shown that bronchial and skeletal muscle receptors have a similar pattern of response to,-sympathomimetic amines (Bowman & Nott, 1970;Rodger, 1971;Apperley & Daly, 1972;Bowman & Rodger, 1972;Gwee, Nott, Raper & Rodger, 1972). It seems likely, therefore, that the tremorogenic properties of 3-agonist bronchodilator drugs may be inseparable from their bronchial relaxing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Marsden et al (1967) have shown an increase in physiological tremor with isoprenaline and have demonstrated a blockade of this induced tremor by propranolol, suggesting that a 3 receptor may be involved. Animal studies have shown that bronchial and skeletal muscle receptors have a similar pattern of response to,-sympathomimetic amines (Bowman & Nott, 1970;Rodger, 1971;Apperley & Daly, 1972;Bowman & Rodger, 1972;Gwee, Nott, Raper & Rodger, 1972). It seems likely, therefore, that the tremorogenic properties of 3-agonist bronchodilator drugs may be inseparable from their bronchial relaxing properties.…”
Section: Discussionmentioning
confidence: 99%
“…produces vasodepressor and positive chronotropic effects, antagonizes serotonin-induced increases in pulmonary resistance, and depresses soleus muscle contractility (Gwee et al, 1972). In terms of the dual P-adrenoceptor classification developed by Lands and his CO-workers (Lands et al, 1967), it would appear that MJ9184-1 possesses some degree of selectivity in stimulating /?,-(bronchodilator) as opposed to /?,-(cardiac) adrenoceptors (Gwee et al, 1972).…”
mentioning
confidence: 99%
“…The method allows the construction of reproducible dose-response curves. It is relatively quick, and is especially useful when assessing the potencies of longacting sympathomimetic bronchodilators.In previous experiments carried out in this laboratory the relative potencies of sympathomimetic bronchodilators in cats were assessed by measuring the abilities of graded doses to antagonize bronchoconstriction produced by a constant repeated dose of serotonin (Bowman & Rodger, 1972;Gwee et al, 1972;Rodger, 1973). In the experiments described in this paper, a constant level of bronchoconstriction was produced by a continuous infusion of serotonin, and each sympathomimetic amine was injected cumulatively.…”
mentioning
confidence: 99%